Constant hepatic ATP concentrations during prolonged fasting and absence of effects of Cerbomed Nemos(®) on parasympathetic tone and hepatic energy metabolism. - Gancheva,S; Bierwagen,A; Markgraf,DF; Bönhof,GJ; Murphy,KG; Hatziagelaki,E; Lundbom,J; Ziegler,D; Roden,M (Molecular Metabolism, 2017)
OBJECTIVE: Brain insulin-induced improvement in glucose homeostasis has been proposed to be mediated by the parasympathetic nervous system. Non-invasive transcutaneous auricular vagus nerve stimulation (taVNS) activating afferent branches of the vagus nerve may prevent hyperglycemia in diabetes models. We examined the effects of 14-min taVNS vs sham stimulation by Cerbomed Nemos(®) on glucose metabolism, lipids, and hepatic energy homeostasis in fasted healthy humans (n = 10, age 51 ± 6 yrs, BMI 25.5 ± 2.7 kg/m(2)). METHODS: Heart rate variability (HRV), reflecting sympathetic and parasympathetic nerve activity, was measured before, during and after taVNS or sham stimulation. Endogenous glucose production was determined using [6,6-(2)H2]glucose, and hepatic concentrations of triglycerides (HCL), adenosine triphosphate (ATP), and inorganic phosphate (Pi) were quantified from (1)H/(31)P magnetic resonance spectroscopy at baseline and for 180 min following stimulation. RESULTS: taVNS did not affect circulating glucose, free fatty acids, insulin, glucagon, or pancreatic polypeptide. Rates of endogenous glucose production (P = 0.79), hepatic HCL, ATP, and Pi were also not different (P = 0.91, P = 0.48 and P = 0.24) between taVNS or sham stimulation. Hepatic HCL, ATP, and Pi remained constant during prolonged fasting for 3 h. No changes in heart rate or shift in cardiac autonomic function from HRV towards sympathetic or parasympathetic predominance were detected. CONCLUSION: Non-invasive vagus stimulation by Cerbomed Nemos(®) does not acutely modulate the autonomic tone to the visceral organs and thereby does not affect hepatic glucose and energy metabolism. This technique is therefore unable to mimic brain insulin-mediated effects on peripheral homeostasis in humans.